EFEKTIVITAS PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN MINAT BELAJAR SISWA - Harianti, Utari; Haeril; Hamka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of contextual learning in increasing students’ learning interest. The research was conducted in Class X of UPT SMAN 25 Bone with a total sample of 57 students. The study employed a Pre-Experimental Design with a quantitative data analysis technique.The results showed an increase in the average learning interest score from 31.02 before the treatment to 32.86 after the treatment. Based on the paired sample t-test, the increase was statistically significant (p < 0.05).Thus, it can be concluded that contextual learning is effective in enhancing students’ learning interest. These findings recommend that teachers apply contextual learning as one of the strategies to improve students’ learning interest.